Escherichia coli, Pathogenicity of Escherichia coli,Virulence Factors of Escherichia coli, Secreted Virulence (Short Review) - Mohsen, Rana Talib (Asian Journal of Science, Technology, Engineering, and Art, 2025)
The Enterobacteriaceae family of facultative anaerobic, Gram-negative, glucose-fermenting bacteria that are catalase positive and oxidase negative is associated with almost all CUAI, whereas UTIs are particularly closely related. The bacterial species E. Coli is broad and varied. Some strains of Escherichia coli can cause lung infections, pneumonia, diarrhea, and urinary tract infections (UTIs). In natural settings, both biotic and abiotic variables can affect E. Coli's ability to survive and develop. The obtainability of nutrients and water, temperature, pH, and sunlight are examples of abiotic variables. E. Coli's capacity to obtain nutrients, contest with other microbes, and create biofilms outside is one example of a biologic challenge.